IMPLEMENTASI PENGGUNAAN EDPUZZLE DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PERSONALIZED LEARNING - Sugiarto, Silvia Rani Nazua; Magdad Hatim; Ida Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to investigate the implementation of Edpuzzle as a learning media to improve students learning outcomes in Sciences and Social Studies (IPAS) through the use of a personalized learning model. This reserch employed a qualitative approach with a descriptive method. The subjects of the study were elementary school students whose data were collected through observation, interviews, and documentation. The finding revealed that the use of Edpuzzle effectively enhanced student engagement, facilitated better understanding of the material, and provided a learning experiences tailored to each student’s need and pace. The personalized learning model applied in this study supported students-centered learning and had a positive impact on improving learning outcomes.